2023
DOI: 10.3171/2022.6.spine211559
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic acute failure of pelvic fixation in adult spinal deformity requiring revision surgery: a multicenter review of incidence, failure mechanisms, and risk factors

Abstract: OBJECTIVE There are few prior reports of acute pelvic instrumentation failure in spinal deformity surgery. The objective of this study was to determine if a previously identified mechanism and rate of pelvic fixation failure were present across multiple institutions, and to determine risk factors for these types of failures. METHODS Thirteen academic medical centers performed a retrospective review of 18 months of consecutive adult spinal fusions extending 3 or more levels, which included new pelvic screws a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…At our institution, we identified a 5% acute pelvic fixation failure rate over an 18-month period 10 . In a subsequent multicenter retrospective series, a similar 5% acute pelvic fixation failure rate was also reported 11 . In response to these findings, our institution changed its pelvic fixation strategies to incorporate multiple points of pelvic fixation.…”
supporting
confidence: 53%
“…At our institution, we identified a 5% acute pelvic fixation failure rate over an 18-month period 10 . In a subsequent multicenter retrospective series, a similar 5% acute pelvic fixation failure rate was also reported 11 . In response to these findings, our institution changed its pelvic fixation strategies to incorporate multiple points of pelvic fixation.…”
supporting
confidence: 53%
“…A recent multicenter study found a slightly higher rate of screw failure with IS than that with S2AI in the univari-ate analysis, with no significant difference in the multivariate analysis. 19 Another recent multicenter study found higher loosening rate of pelvic screw in the S2AI group than that in the IS group and higher rod fracture rate in the IS group than that in the S2AI group. 18 In a study by Cho et al, 34 involving 45 cases, the S2AI had a higher failure rate than the IS (35% vs. 12%).…”
Section: Discussionmentioning
confidence: 94%
“…14,24 In this meta-analysis, we pooled data from 10 cohort studies comparing the IS and S2AI fixation techniques in adult patients. 11,13,14,18,19,[24][25][26][27][28] Analysis of the outcomes based on the implant failure showed that the pooled proportion of patients with implant failure was not statistically different between the 2 techniques: 21.9% with IS and 18.9% with S2AI, respectively (p= 0.59). However, analysis based on revision, screw prominence, and wound complications showed that the pooled proportion of patients with each complication was higher in the IS group than that in the S2AI group (revision, IS: 21.0% vs. S2AI: 8.5%, p= 0.02; screw prominence, IS: 9.6% vs. S2AI: 0.0%, p< 0.01; wound complications, IS: 31.7% vs. S2AI: 3.9%, p < 0.01).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations